Analysis of the Impact of Globalization on International Trade - Bernando Aldo Yosua Tambunan; Putri Ananda; Eka Saripa Br. Siburian; Khairani Alawiyah Matondang; Riza Indriani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Through international trade activities, it will be formed connection each other dependency Among countries which there is in world this, where something country may need commodities that cannot be produced independently in their country but are owned by other countries. This research was conducted with the aim of knowing and explaining